Artificial Neural Networks for Pyrolysis, Thermal Analysis, and Thermokinetic Studies: The Status Quo - Muravyev, Nikita V; Luciano, Giorgio; Ornaghi, Heitor Luiz, Jr; Svoboda, Roman; Vyazovkin, Sergey (MDPI, 2021)
Artificial neural networks (ANNs) are a method of machine learning (ML) that is now widely used in physics, chemistry, and material science. ANN can learn from data to identify nonlinear trends and give accurate predictions. ML methods, and ANNs in particular, have already demonstrated their worth in solving various chemical engineering problems, but applications in pyrolysis, thermal analysis, and, especially, thermokinetic studies are still in an initiatory stage. The present article gives a critical overview and summary of the available literature on applying ANNs in the field of pyrolysis, thermal analysis, and thermokinetic studies. More than 100 papers from these research areas are surveyed. Some approaches from the broad field of chemical engineering are discussed as the venues for possible transfer to the field of pyrolysis and thermal analysis studies in general. It is stressed that the current thermokinetic applications of ANNs are yet to evolve significantly to reach the capabilities of the existing isoconversional and model-fitting methods.
Umělé neurální sítě pro pyrolýzu, termální analýzu a termokinetické studie: Status Quo
Keywords: artificial neural networks; conversion degree; kinetics; machine learning; pyrolysis; thermal analysis; umělá neurální síť; stupeň konverze; kinetika; strojové učení; pyrolýza; termická analýza